Prevalence of risk factors for denture stomatitis in complete denture wearers - Morel, Laura Lourenço (2019)
Aim: The prevalence of denture stomatitis and the relationship with its risk factors was evaluated via secondary data from 62 complete denture (CD) wearers, between 2015 and 2017. Methods: The data was stored in an Excel database and was analyzed using the statistics software STATA/SE 12.0. A descriptive analysis was performed taking into account a categorization of the clinical variables according to risk factor in 4 domains:  CD usage, systemic health, hygiene habits, and usage habits. The association amongst the denture stomatitis and risk factors variables was tested by the Chi-square test and the results were statistically significant at p-values <0.05. Results: The CD wearers participants were composed by a majority of elderly (80.64%) and women (72.78%); with 45.16% having been using the current denture for more than 10 years and another 74.19% related a continuous usage. Diabetes and hypertension were related by 83.87% and 67.74%, respectively, with 87.10% using medication. Although 75.80% reported cleaning their dentures 3 times per day or more, and 59.68% considered their oral hygiene very good, 50% of the complete dentures showed dirtiness and clinical signs of Denture Stomatitis were present in 30.64% of the patients. Despite of the evaluated sample shows many risk factors for the development of the disease, an association between the variables was not observed. Conclusion: Considering the high prevalence of the disease in the studied sample, preventive and educational measures on denture usage and hygiene must be reinforced in order to maintain the oral health of the edentulous patients.